The Addition Effect Of Active Carbon From Waste of Ambon Lumut Banana Peel ( Musa acuminata Colla) on Decreasing Peroxide in Used Cooking Oil - Novriyanti Lubis; Esty Rahayu Pangestika; Dang Soni (Farmasains : Jurnal Ilmiah Ilmu Kefarmasian, 2023)
High temperature, repeated, and oxidized heating process will experience used cooking oil damage. Peroxide number is the most important value to determine the degree of damage the oil. The purpose of this study was to see the effect of soaking with activated carbon from Ambon Lumut banana peels with different activators on decreasing the peroxide value in used cooking oil, determining the analysis was carried out using the iodometric method. The results were obtained after soaking banana peel activated carbon with HCl activator in used cooking oil samples from frying chicken, fried snacks, and 2 times the use of each % decreased peroxide number by 82.26%; 30.90% and 68.88%, while the ZnCl2 activator in these samples decreased by 85.22%; 51.82% and 92.77%. The use of ZnCl2 activator gives the best results in reducing the peroxide value in used cooking oil.